Regulation of Myosin Light-Chain Phosphatase Activity to Generate Airway Smooth Muscle Hypercontractility - Álvarez-Santos, Mayra D.; Álvarez-González, Marisol; Estrada-Soto, Samuel; Bazán-Perkins, Blanca (Frontiers in Physiology, 2020)
Smooth muscle is a central structure involved in the regulation of airway tone. In addition, it plays an important role in the development of some pathologies generated by alterations in contraction, such as hypercontractility and the airway hyperresponsiveness observed in asthma. The molecular processes associated with smooth muscle contraction are centred around myosin light chain (MLC) phosphorylation, which is controlled by a balance in the activity of myosin light-chain kinase (MLCK) and myosin light-chain phosphatase (MLCP). MLCK activation depends on increasing concentrations of intracellular Ca2+, while MLCP activation is independent of Ca2+. MLCP contains a phosphatase subunit (PP1c) that is regulated through myosin phosphatase target subunit 1 (MYPT1) and other subunits, such as glycogen-associated regulatory subunit and myosin-binding subunit 85 kDa. Interestingly, MLCP inhibition may contribute to exacerbation of smooth muscle contraction by increasing MLC phosphorylation to induce hypercontractility. Many pathways inhibiting MLCP activity in airway smooth muscle have been proposed and are focused on inhibition of PP1c, inhibitory phosphorylation of MYPT1 and dissociation of the PP1c-MYPT1 complex.